Meruntuhkan Pilar Keadilan: Apakah Sistem Peradilan Dapat Berfungsi Tanpa Standar Pembuktian? - Zul Khaidir Kadir (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The standard of proof is the foundation that keeps the criminal justice system from turning into a repressive tool to prevent state power from imposing arbitrary sentences. However, in the midst of technological developments, it has created an unstable evidence landscape that threatens the continuity of the legitimacy of the law itself without a standard of proof that can be objectively verified. This study uses a qualitative research method with a conceptual approach. The data collection method is collected using literature studies, then analyzed using qualitative methods and presented descriptively. The results of the study show that maintaining the existence of the standard of proof is no longer adequate if it is not accompanied by a responsible and adaptive reformulation to the complexity of contemporary evidence. Exploration of alternative forms of evidence offers opportunities to increase precision and transparency that have been difficult to achieve with traditional mechanisms, but all of these innovations can only contribute constructively if they are placed within a strict legal and ethical framework, given the inherent risks such as algorithmic bias, the reduction of judicial convictions to statistics without context, and gaps in accountability between jurisdictions in the application of forensic technology.